2008
DOI: 10.1088/0953-8984/20/10/104220
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterisation of a Ni–Fe-based superalloy byin situsmall-angle neutron scattering measurements

Abstract: The microstructural evolution at high temperatures was studied in an experimental Ni–Fe-based superalloy DT706 by in situ small-angle neutron scattering (SANS). Modifying the alloy heat treatment to improve the microstructural stability and mechanical properties in Inconel 706 type superalloys has been a significant research goal for many years. The earlier studies of phase transformation relied mostly on optical and electron microscopy investigations of samples that were cooled down to room temperature after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Complementary in-situ and ex-situ small-angle neutron scattering (SANS) investigations were performed to get representative information from larger volumes about the temporal evolution of the γ precipitate phase. Previous studies demonstrated that two-phase superalloys can be successfully analyzed by SANS to investigate the microstructural evolution of the γ/γ microstructure during heat treatments [14][15][16][17][18]. In this study, the γ precipitate size distributions and volume fractions during the heat treatment procedures and after the full three-step heat treatment were determined quantitatively.…”
Section: Introductionmentioning
confidence: 98%
“…Complementary in-situ and ex-situ small-angle neutron scattering (SANS) investigations were performed to get representative information from larger volumes about the temporal evolution of the γ precipitate phase. Previous studies demonstrated that two-phase superalloys can be successfully analyzed by SANS to investigate the microstructural evolution of the γ/γ microstructure during heat treatments [14][15][16][17][18]. In this study, the γ precipitate size distributions and volume fractions during the heat treatment procedures and after the full three-step heat treatment were determined quantitatively.…”
Section: Introductionmentioning
confidence: 98%
“…[3] In the 718-type Ni-based superalloys, the austenitic matrix (c phase) is strengthened by intermetallic precipitates of Ni 3 Al (c¢, fcc L1 2 structure) and Ni 3 Nb (c¢¢, bct DO 22 structure), and the existence of coprecipitates of both phases with different morphologies (plate, needle, cube, or disc shape) was also observed. [4,5] Other phases that can also be formed are Ni 3 Nb-based (d, orthorhombic DO a structure) and Ni 3 Ti-based (g, hexagonal DO 24 structure). The limiting service temperature (650°C) of alloy 718 is due to the instability of the c¢¢ phase, which transforms into d phase, and the alloy loses its creep resistance.…”
Section: Introductionmentioning
confidence: 99%
“…While ex-situ SANS brings information on precipitate morphology, size and specific interface in superalloys (see e.g., [8,9] and references therein), in-situ SANS studies, moreover, are able to follow the evolution of the microstructure of superalloys directly at high temperature [10][11][12][13][14]. This approach has important benefits when compared with room temperature measurements, as the Table 1.…”
Section: Introductionmentioning
confidence: 99%